Implementasi Augmented Reality dalam Pembelajaran Interaktif Mata Pelajaran Huruf Hijaiyah untuk Siswa Sekolah Dasar Swasta Muhammadiyah Labuan - Alriyadi, Muhammad Irzi Ghaits; Hassan, Albiyan Ardli (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The purpose of this research is to develop an Augmented Reality application for learning Hijaiyah letters at Muhammadiyah Labuan Elementary School. Teachers often struggle to make lessons engaging, as available media are limited to books and whiteboards. As a result, many students lose interest and find it difficult to stay focused during class. To address these challenges, the application was designed using Unity 3D as the main platform, combined with Vuforia Engine for marker scanning and Blender for creating 3D models of Hijaiyah letters. The development process followed the Rapid Application Development (RAD) stages, starting from needs analysis through observation and interviews, system design, and continuing to implementation and testing. Trials were conducted on Android devices involving both students and teachers. The results show that the application can display Hijaiyah letters interactively, complete with audio pronunciation, making it easier for students to recognize both the shape and sound of each letter. Over 80% of students reported that learning became more enjoyable and easier to understand, while teachers found it helpful for delivering lessons. The use of Augmented Reality has proven effective in boosting students’ interest and understanding of Hijaiyah letters at the elementary level.